Older drivers: On-road and off-road test results - Selander, H.; Lee, Hoe; Johansson, K.; Falkmer, Torbjorn (Elsevier Science, 2011)
Eighty-five volunteer drivers, 65–85 years old, without cognitive impairments impacting on their driving were examined, in order to investigate driving errors characteristic for older drivers. In addition, any relationships between cognitive off-road and on-road tests results, the latter being the gold standard, were identified. Performance measurements included Trail Making Test (TMT), Nordic Stroke Driver Screening Assessment (NorSDSA), Useful Field of View (UFOV), self-rating driving performance and the two on-road protocols P-Drive and ROA. Some of the older drivers displayed questionable driving behaviour. In total, 21% of the participants failed the on-road assessment. Some of the specific errors were more serious than others. The most common driving errors embraced speed; exceeding the speed limit or not controlling the speed. Correlations with the P-Drive protocol were established for NorSDSA total score (weak), UFOV subtest 2 (weak), and UFOV subtest 3 (moderate). Correlations with the ROA protocol were established for UFOV subtest 2 (weak) and UFOV subtest 3 (weak). P-Drive and self ratings correlated weakly, whereas no correlation between self ratings and the ROA protocol was found. The results suggest that specific problems or errors seen in an older person's driving can actually be “normal driving behaviours”.